GIVING OF LIME AND HONEY MASKS TO ADOLESCENT WOMEN WITH ACNE VULGARIS DURING MENSTRUATION AT THE HURUN INN PETERONGAN JOMBANG HOSTEL: A CASE STUDY - Siti Roudhotul Jannah; Muzayyaroh Muzayyaroh; Syafira Ayu Nurellia Fajrin; Good Nur Abidah (Bajang Institute, 2021)
Acne vulgaris occurs due to clogged pores resulting in thickening of the skin at the opening of the holes which occurs due to increased oil production in the oil glands (sebaceous glands). The cause of acne in young women is because they often eat oily foods such as fried foods and lack of rest due to school and dormitory activities which can trigger acne. (Suryoprajogo, Nadine: 2012).The purpose of this study was to provide midwifery care to young women Ms.